Noble metal-free bis-tridentate benzimidazole zinc(ii) and iron(ii) complexes for selective CO2 photoreduction. Issue 10 (17th February 2022) - Liu, Ting; Chen, Longxin; Chao, Duobin
Abstract : A bis-tridentate benzimidazole iron(ii ) complex is found to be much more efficient than the corresponding zinc(ii ) complex in CO2 photoreduction. Abstract : Three noble metal-free metal complexes [Fe(Me-bzimpy)2 ] 2+ (Fe1 ), [Fe(bzimpy)2 ] 2+ (Fe2 ) and [Zn(Me-bzimpy)2 ] 2+ (Zn1 ) were synthesized and studied in the visible light-driven CO2 reduction, where ligands bzimpy and Me-bzimpy were 2, 6-bis(1-methyl-1 H -benzo[ d ]imidazol-2-yl)pyridine and 2, 6-bis(1 H -benzo[ d ]imidazol-2-yl)pyridine, respectively. It was found that Fe1 displayed the best photocatalytic performance with a turnover number (TON) of 878 and high selectivity up to 99.2% towards CO generation in the presence of an organic thermally activated delayed fluorescence (TADF) photosensitizer, which was more than 10 times that of Fe2 (TONCO = 63) and Zn1 (TONCO = 53). This is attributed to the much higher stability of Fe1 upon reduction, as proved by the cyclic voltammograms of the three complexes. These results highlight the cooperation of ligands and metals in molecular metal complexes for CO2 photoreduction.